The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1365-2605.1999.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

To store or mature spermatozoa? The primary role of the epididymis

Abstract: The function of the epididymis is considered in the context that it is necessary to transport spermatozoa for internal fertilization, but is also an adaptation involved in the competition between males to achieve paternity. Post-testicular sperm maturation and storage occur in lower vertebrates, such as the chondrichthyes, in which sperm storage is essential due to the slow rate of spermatogenesis. These roles persist in higher vertebrates, including mammals. However, they are less important in certain birds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 77 publications
1
101
0
4
Order By: Relevance
“…5) suggests the possibility that RHOX10 has a function in the caput. For example, RHOX10 might promote sperm maturation, as this is known to occur in the caput (Cosentino & Cockett 1986, Jones 1999. We previously showed that another member of the Rhox gene cluster selectively expressed in the caput -Rhox5 -promotes the acquisition of sperm forward motility (Rao et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…5) suggests the possibility that RHOX10 has a function in the caput. For example, RHOX10 might promote sperm maturation, as this is known to occur in the caput (Cosentino & Cockett 1986, Jones 1999. We previously showed that another member of the Rhox gene cluster selectively expressed in the caput -Rhox5 -promotes the acquisition of sperm forward motility (Rao et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…It is also essential that the epididymides accumulate and store sperm as, depending upon species, it takes 0.5 to 2 days for the testes to produce the number of sperm in a normal ejaculate, and in a competitive mating system 30 males may inseminate up to 50 females in a day (Jones, 1999;Jones et al, 2007). The efficacy of sperm storage in the epididymis is so high that fertile sperm can survive in an isolated epididymis for several days at 4°C (GuĂ©rin et al, 2003) The epididymis is a very long duct which receives testicular sperm via the efferent ducts.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the chelonians from temperate regions that reproduce seasonally, the spermatozoa produced during the summer are stored in the epididymides and are used in matings that occur throughout the year (Jones, 1999;Gist et al, 2000).…”
mentioning
confidence: 99%